Structure analysis and antiviral activity of CW-33 analogues against Japanese encephalitis virus. Issue 1 (December 2018) - Lien, Jin-Cherng; Wang, Ching-Ying; Lai, Hsueh–Chou; Lu, Chien-Yi; Lin, Yu-Fong; Gao, Ging-Yan; Chen, Kuan-Chung; Huang, An-Cheng; Huang, Su-Hua; Lin, Cheng-Wen
Abstract Japanese encephalitis virus (JEV) is a member of neurotropic flaviviruses transmitted by mosquito bites, causing severe central nervous system disorders. Current JEV genotype III vaccines have a low protection against genotype I isolates in the risk zone. The lead compound CW-33, ethyl 2-(3′, 5′-dimethylanilino)-4-oxo-4, 5-dihydrofuran-3-carboxylate, demonstrates the antiviral activity against JEV with an IC50 values of 38.5 μM for virus yield reduction (Int J Mol Sci 2016, 17: E1386). This study synthesized fourteen CW-33 analogues containing a fluoro atom or one methoxy group at the C-2, C-3, or C-4 of anilino ring, and then evaluated for their antiviral activity and mechanism. Among 6 amalogues, CW-33A (ethyl 2-(2-fluoroanilino)-4-oxo- 4, 5-dihydrofuran-3-carboxylate), and CW-33D (ethyl 2-(3-methoxyanilino)-4-oxo- 4, 5-dihydrofuran-3-carboxylate exhibited antiviral potentials in viral cytopathic effect (CPE) inhibition. CW-33A significantly suppressed the viral protein expression, genome synthesis and intracellular JEV particle production, showing a higher inhibitory effect on JEV yield than CW-33 and CW-33D. The study demonstrated that a mono-fluoro substitution on at the C-2 anilino ring of CW-33 improved the antiviral activity JEV, revealing the structure-activity relationship for developing novel agents against JEV infection.